The Role of Financial Literacy and Grit in Good Financial Behavior: Peran Literasi Keuangan dan Ketabahan dalam Perilaku Keuangan yang Baik - Endah Amaliyah, Erlina Dewi; Prabasari, Bonita; Rohmawati, Lilik (Universitas Muhammadiyah Sidoarjo, 2023)
With Generation Z and millennials becoming the majority of Indonesia's population, tackling their reputation for financial wastefulness becomes critical. Through the promotion of financial literacy, this study intends to provide insights into developing wiser and more sensible financial conduct. Recognizing the inconsistency of past studies on financial literacy and behavior, this study incorporates grit as a moderating component. Data was acquired through surveys distributed around Semarang City and analyzed in Smart PLS utilizing path analysis. Financial literacy was determined by understanding the time worth of money, inflation, and risk diversification, whereas grit was determined by perseverance and constant interest. Credit management, investment, saving, cash flow and consumption, emergency fund management, and retirement fund planning were all evaluated. The findings show that grit has a positive influence on financial behavior, emphasizing the need of perseverance in the face of financial obstacles. Furthermore, financial literacy was discovered to have a favorable impact on grit, emphasizing the symbiotic relationship between knowledge and perseverance in accomplishing financial goals. This study emphasizes the importance of not just improving financial literacy but also cultivating grit among Generation Z and millennials in order to improve financial behavior.